Dignity at Work: Integrating Christian Social Teachings and Sustainable Development Goals in the Labour Landscape of Sri Lanka - Paul Rohan, J.C. (Maheswari Publishers, 2026)
This article explores the concept of ̳work with dignity ̳ in Sri Lanka through an interdisciplinary integration of Christian Social Teaching (CST) and the United Nations Sustainable Development Goals (SDGs), particularly SDG 8.5, which targets full and productive employment, decent work, and equal pay for all. Drawing on foundational CST encyclicals such as Rerum Novarum (1891), Laborem Exercens (1981), and Fratelli Tutti (2020), it posits work as a divine vocation that affirms human dignity, critiques exploitative systems, and promotes solidarity, subsidiarity, and the common good. In Sri Lanka ̳s labour landscape - marked by colonial legacies, ethnic conflicts, the Covid-19 pandemic, the 2022 economic crisis, and persistent inequities in plantations, garments, and informal sectors - these principles address structural challenges like gender wage gaps (20 - 30%), informal employment (over 60%), and minority discrimination. By synthesising theological ethics with empirical data and International Labour Organization (ILO) frameworks, the analysis identifies convergences between CST ̳s moral imperatives and SDG 8.5 ̳s policy targets, proposing pathways for ethical reforms: community cooperatives for full employment, rights- based protections for decent work, and justice-oriented audits for equal pay. This holistic approach transcends economic metrics, envisioning labour as integral to human flourishing. Ultimately, the integration offers Sri Lanka a transformative agenda, enriching SDG implementation with CST ̳s prophetic vision to foster just, sustainable economies rooted in the inherent worth of every worker.
Keywords: Christian social teaching (CST); Dignity of work; Sri Lankan labour; Sustainable development goals (SDGs); Decent employment